ABC News - American Agenda: National Foundation for Teaching Entrepreneurship
ABC host Peter Jennings presents the “American Agenda” in which he speaks about high-school teacher Steve Mariotti and a small community of children from Bronx who were thought business skills and encouraged to be entrepreneurs as an alternative to drug trafficking and other illegal economic activities.